Modular architecture principles–MAPs: a key factor in the development of sustainable open architecture products (2019)
Modularity is one of the most useful tools employed in the product development process. Regarding functionality, the use of modules is common to generate flexible platforms to manufacture products and product families that require functional variations. In the current globalized market, the mass individualization or personalization is the preferred production model that delivers cost-effectiveness and satisfaction at the level of the market of one. In this model, the modularity is employed as a powerful concept applied not only for the manufacture but also for the use and final disposal stages, in which the design of modules provides functionalities and features that satisfy a variety of specifications for different market segments. Despite the existence of approaches in modularity and its usefulness in product development, it is possible to identify a lack of analysis of modular and open architecture to enhance the sustainability performance of products regarding strategies to diminish adverse impacts during their lifecycle. This paper provides an analysis of the influence and potential of Modular Architecture Principles–MAPs in the sustainable design of open architecture products. Additionally, lifecycle considerations are analysed to identify and propose strategies that enforce the sustainability performance of products concerning personalization from early design stages Abbreviations: MAPs: Modular Architecture Principles; FMS: Flexible Manufacturing System; RMS: Reconfigurable Manufacturing System; EOL: End Of Life; LCA: Life Cycle Assessment; QFD: Quality Function Deployment; DFMA: Design For Manufacturing And Assembly. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.